Pembatalan Akta Pembagian Harta Waris Yang Didasarkan Pada Hukum Adat Batak Toba (Studi Putusan Mahkamah Agung Nomor 909 PK/PDT/2019) - Simanjuntak, Solagratia Moza Tessalonika; Yustikarini, Meliyana (Universitas Batanghari Jambi, 2024)
This research aims to analyze the legal consequences of Supreme Court Decision Number 909 PK/Pdt/2019 on inheritance according to Toba Batak Customary Law, and analyze the role of notaries in making a Deed of Testament containing the will of the confronter to inherit based on Toba Batak Customary Law. This doctrinal research uses secondary data in the form of legal materials relevant to Inheritance Law and Toba Batak Customary Law. The legal effect of the Decision a quo on inheritance based on Toba Customary Law is that the Deed of Testament is declared defective and null and void because it violates statutory provisions. In addition, it can also be stated that there has been a shift in inheritance in the Toba Batak Customary Society, which initially adhered to patrilineal legal norms to begin to accommodate equal rights between sons and daughters. In relation to the role of notaries in the preparation of Testament Deeds based on Toba Batak Customary Law, it can be stated that legal counseling on inheritance must be delivered before making a deed so that the confronter can understand the legal provisions he chooses to use as the basis for inheritance. In addition, the notary can make clauses in the Deed of Testament to clarify the intentions contained in the deed, especially in the context of the distribution of inheritance made based on the last will of the testator.